Developing Students' Creative Thinking Potential - Hamroyev Jamshid Abduqodir ugli (Euro Asian Journal Publishing, 2024)
The article is devoted to the problem and the need to develop creative thinking of undergraduate students in the learning process. The essence and types of thinking, the essence of creative thinking, the features of the development and diagnosis of creative thinking of undergraduate students in the learning process are considered.
Keywords: thinking; creativity; creative thinking; diagnostics of creative thinking